Desenvolvimento de um método de solubilização de nanotubos de carbono e sua aplicação em imunoensaios - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Since they were discovered, the carbon nanotubes have attracted the interest of many researchers due to their physical, chemical and electronic properties that allow its application in different areas of knowledge, including biomedical applications. Carbon nanotubes may be used as nanosensors and used as pathogens detection sensor. However, for application in immunoassays there must be a good solubilization of these carbon nanotubes. The problem for a good solubilization is aggregation of carbon nanotubes which reduces the important properties of these materials, proposals for a single nanotube. This study sought a method for solubilization of carbon nanotubes and their application in lateral flow systems. For this they used recombinant proteins ( "protein 2" rich in Histidine, HRP2) already obtained in previous work. In addition, the physical characteristics of carbon nanotubes was obtained through analysis by Raman spectroscopy, absorption spectroscopy in the ultraviolet-visible region (UV-Vis) spectroscopy in the infrared Fourier transform (FTIR) was performed. And its dispersion and functionalization was measured by flow cytometry. This work showed that methodology dispersion of carbon nanotubes allows their use in lateral flow systems. What makes it interesting not only for the detection of malarial antigens demonstrated in this study, but also for other applications in detection methods. This carbon nanotube solubilization methodology makes these nanotubes applicable in Immunoassays, chromatography and molecular tests.
Keywords: Nanotubos de carbono; Imunoensaios; Biosensores; Imunocromatografia de fluxo lateral; CIÊNCIAS DA SAÚDE